Surgical Pathology of the Gastrointestinal System: Bacterial, Fungal, Viral, and Parasitic Infections - Lamps, Laura W.; SpringerLink (Online service) (New York, NY : Springer US, 2010)
Surgical Pathology of the Gastrointestinal System: Bacterial, Fungal, Viral, and Parasitic Infections provides a unique diagnostic reference text for the pathologic diagnosis of infectious diseases of the gastrointestinal tract. Written for the practicing surgical pathologist, this text combines the superior illustrations of an atlas with carefully written prose to create a useful diagnostic companion. The text is divided into four sections covering bacterial, fungal, viral, and parasitic infections of the gastrointestinal tract. The descriptive sections of each chapter are organized into short paragraphs for easy reference and include the use of tables to compare and contrast organisms and summarize differential diagnoses. Each chapter is extensively illustrated, and contains prose discussions of diagnostic features, differential diagnoses, brief clinical descriptions, and ancillary tests that help confirm the diagnosis (i.e. immunohistochemistry, special histochemical stains, and molecular diagnostic techniques). Surgical Pathology of the Gastrointestinal System: Bacterial, Fungal, Viral, and Parasitic Infections provides pertinent clinical, diagnostic, and epidemiologic information that will be valuable to the practicing surgical pathologist. This volume will also help surgical pathologists gain familiarity with other contributory laboratory tests that are available to help confirm diagnosis.
Section I. Bacterial Infections of the Gastrointestinal Tract -- General Approach to the Diagnosis of Gastrointestinal Infections -- Aeromonas, Vibrio cholerae, and Related Bacteria -- Campylobacter Species -- Helicobacter pylori and Related Species -- Salmonella Species -- Shigella Species -- Escherichia coli Species -- Yersinia enterocolitica and Yersinia pseudotuberculosis -- Mycobacterial Infections -- Clostridial Infections -- Spirochetes -- Whipple's Disease -- Miscellaneous Bacterial Infections -- Section II. Fungal Infections of the Gastrointestinal Tract -- General Approach to Diagnosis of Fungal Infections of the Gastrointestinal Tract -- Candida Species -- Aspergillus Species and Zygomycetes -- Histoplasmosis -- Cryptococcus neoformans -- Pneumocystis carinii -- Section III. Viral Infections of the Gastrointestinal Tract -- Cytomegalovirus -- Herpes Simplex Virus -- Adenovirus -- Miscellaneous Enteric Viruses -- Human Papillomaviruses -- Human Immunodeficiency Virus -- Miscellaneous Viral Infections -- Section IV. Parasitic Infections of the Gastrointestinal Tract -- Miscellaneous Protozoal Infections -- Entamoeba histolytica -- Intestinal Flagellates -- Coccidians -- Miscellaneous Helminthic Infections -- Enterobius vermicularis (Pinworms) -- Strongyloides stercoralis -- Anisakis Simplex and Related Nematodes -- Schistosomiasis.
Keywords: Medicine; Gastroenterology; Emerging infectious diseases; Pathology; Medicine & Public Health; Pathology; Gastroenterology; Infectious Diseases